Archi Mation: an animation production centre in Bloemfontein as appoint of convergence between architecture and animation - Eke, Clarise (University of the Free State, 2022)
Despite their differences, animation and architecture have similar conceptual and practical approaches to the design and construction of framed areas and spatial organization. The common ground between theoretical and practical methods in both domains with regard to frames and space is the subject of the thesis. A problem arises when a closed off urban scape which allows no easy access becomes a no man’s land, and the thesis project sets itself to resolve the problem through research, design and critical solutions. The following research question guides the study and design process: Which architectural mechanisms can serve as tools to address the inaccessibility of the urban scape, allowing urban dwellers more ease of access? This focus aims to lead towards an architectural and critical response and hopes to unearth the necessary steps to unveil the above mechanisms. The study analyses not only theoretical and practicalities of both the architectural and the animation domains but exhibits and magnifies the spaces which is created when they meet and evidently create hybridity between the two. The merging of spaces creates architectural opportunities through the translation of animation and architecture while conceptual approaches and site analysis aids in forming spatial qualities. These spatial qualities are products of hybrid elements, linking to the research question and answering it with specific and substantiated relevant elements.
Dissertation(M.Arch. (Architecture))--University of the Free State, 2022
Keywords: Hybrid; Frames; Realm; Domains; Thresholds; Animation